Sistem Informasi Rumah Moderasi STAIN Bengkalis Menggunakan Metode Research And Development (R&D) - Rahmayani, Mentari Tri Indah; Purbolingga, Yoan; Yolanda, Desta (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to develop the Rumah Moderasi (Moderation House) Information System at STAIN Bengkalis as a platform for information services and reporting, intended to strengthen religious moderation within the campus environment. The research employs the Research and Development (R&D) method using the 4D development model (Define, Design, Develop, and Disseminate). The system is designed to facilitate lecturers and students in accessing information and reporting indications of radicalism online. The test results show that the system has a positive impact in enhancing services and reinforcing values of tolerance and religious moderation in the academic setting. The implementation of this system is expected to encourage the creation of an inclusive, tolerant campus environment that is free from radical ideologies.